PENINGKATAN PERKEMBANGAN AUD - Muhammad Usman (Universitas Serambi Mekkah, 2017)
Physical development in early childhood covers two main areas, namely gross motor and fine motor. Physical development of children goes according to developmental stages. However, as the developments of other dimensions, physical development of children is not running at the same time. Some children experience physical development faster than his friends, and the rest of them run slower. Growth and physical development has a very important role in a child's life. Growth and physical development is one of the tasks of the major developments in the life of a child. Growth and physical development will affect the development and growth of children in other developmental dimensions. Parents and teachers are very necessary to understand the growth and physical development of children, and instill healthy habits through physical activity of children from an early age. To help the physical development of children, the teachers and parents need to provide guidance to them in order to have an awareness of sensory abilities, and also has a positive attitude towards him. Parents and teachers also need to understand the signs of developmental delays in children, parents and teachers need to be cautious in view of delays in the development of children and must consult a doctor to ensure and provide the necessary help children, so that children can grow physically and develop optimally.